Achieving scientific and regulatory success in implementing non-animal approaches to human and veterinary rabies vaccine testing: A NICEATM and IABS workshop report. (July 2019) - Poston, Rebecca; Hill, Richard; Allen, Cynthia; Casey, Warren; Gatewood, Donna; Levis, Robin; Mallet, Laurent; Smith, Dean; Srinivas, Geetha; Stirling, Catrina; Allen, David
Abstract: This two-day workshop, co-sponsored by NICEATM and IABS-NA, brought together over 60 international scientists from government, academia, and industry to advance alternative methods for human and veterinary Rabies Virus Vaccine (RVV) potency testing. On day one, workshop presentations focused on regulatory perspectives related to in vitro potency testing, including recent additions to the European Pharmacopoeia (5.2.14) that provide a scientific rationale for why in vivo methods may be less suitable for vaccine quality control than appropriately designed in vitro methods. Further presentations reviewed the role of the consistency approach to manufacturing and vaccine batch comparison to provide supportive data for the substitution of existing animal-based methods with in vitro assays. In addition, updates from research programs evaluating and validating RVV glycoprotein (G) quantitation by ELISA as an in vitro potency test were presented. On the second day, RVV stakeholders participated in separate human and veterinary vaccine discussion groups focused on identifying potential obstacles or additional requirements for successful implementation of non-animal alternatives to the in vivo potency test. Workshop outcomes and proposed follow up activities are discussed herein. Highlights: Human and veterinary rabies vaccines are required to undergo testing for quality of safety and potency. The traditional test method used is an in vivo test in mice. Ongoing efforts are focused on reducing, refining, and replacing the use of animals for this purpose. This report provides outcomes of an international workshop on implementing nonanimal methods for rabies vaccine testing. Summarizes the most recent regulatory and scientific advancements towards implementing in vitro potency test alternatives.